A College Knowledge Outreach Program for Latino Immigrant Parents: Process and Evaluation - Laura M. Gonzalez (Journal for Social Action in Counseling and Psychology)
As Latino immigrant families adjust to life in the U.S., they may experience individual and systems level barriers to meeting their children’s educational planning needs. In emerging immigrant communities, schools and social service agencies may not have all the resources and structures needed to serve Spanish-speaking parents. Thus, researchers and practitioners may need to consider partnership models to meet the needs of marginalized Spanish-speaking families. The article describes three stages in a community-based college knowledge educational outreach program for Latino parents: (1) needs assessment; (2) collaboration/implementation; and (3) evaluation. The educational outreach program was created and piloted for 27 Latino immigrant parents in two settings (middle school and community agency). The Bryan and Henry (2012) model for collaborative outreach for underserved populations was applied post-hoc to compare the pilot program with an ideal framework and identify possible improvements to the educational outreach program for Latino parents. Implications for program content and the process of community partnering are discussed.